WACANA KONSTRUKTIF PADA PEMBERITAAN KRITIK BEM UI TERHADAP JOKOWI DI MEDIA ONLINE DETIK.COM - M. Naufal Adrian (2023)
This study discusses the construction of discourse on reporting criticism of BEM UI "King of Lip Service" against Jokowi on the online media Detik.com. According to BEM UI, Jokowi's statements not appropriate with reality. Then BEM UI expressed criticism through their social media by giving the nickname "King of Lip Service" using the concept of a meme. This raises pros and cons in society, some consider criticism inappropriate and some consider it permissible. The media is very influential on the social reality that is formed in society. Through the development of news discourse, the media can carry out news construction by eliminating or presenting actors and hiding meanings that have a specific purpose. The method used is descriptive qualitative with data in the form of news discourse written by Detik.com regarding criticism by BEM UI. The researcher uses the discourse analysis technique of Theo Van Leeweun's model by observing the text in news discourse through the Exclusion strategy (presenting actors) and Inclusion (removing actors) with social construction theory of mass media and political economy theory of the media can see how the media constructs news discourse with meaning and hidden purpose. The results of this study indicate that Detik.com in developing a discourse on BEM UI's criticism of "King of Lip Service" towards Jokowi constructs news that tends to corner BEM UI by presenting stronger figures and not giving BEM UI the opportunity to respond in its reporting discourse. The construction that was built by Detik.com is a pseudo partisanship to the society which has purpose of increasing the media's rating or economic income by exploiting the society by writing news that is currently being discussed. Keywords: Criticism of BEM UI "King of Lip Service", Jokowi, Detik.com, Construction of Mass Media Reality, Political Economy of Media, Discourse Analysis of Theo Van Leeweun.